Full-scale experimental verification of resetable semi-active stiffness dampers. - Yang, J. N. (Earthquake engineering & structural dynamics.)
Because of many advantages over other control systems, semi-active control devices have received considerable attention for applications to civil infrastructures. A variety of different semi-active control devices have been studied for applications to buildings and bridges subject to strong winds and earthquakes. Recently, a new semi-active control device, referred to as the resetable semi-active stiffness damper (RSASD), has been proposed and studied at the University of California, Irvine (UCI). It has been demonstrated by simulation results that such a RSASD is quite effective in protecting civil engineering structures against earthquakes, including detrimental near-field earthquakes. In this paper, full-scale hardware for RSASD is designed and manufactured using pressurized gas. Experimental tests on full-scale RSASDs have been conducted to verify the hysteretic behaviours (energy dissipation characteristics) and the relation between the damper stiffness and the gas pressure. The correlation between the experimental results of the hysteresis loops of RASADs and that of the theoretical ones has been assessed qualitatively. Experimental results further show the linear relation between the gas pressure and the stiffness of the RSASD as theoretically predicted. Finally, shake table tests have also been conducted using an almost full-scale 3-storey steel frame model equipped with full-scale RSASDs at the National Center for Research on Earthquake Engineering (NCREE), Taipei, Taiwan, and the results are presented. Experimental results demonstrate the performance of RSASDs in reducing the responses of the large-scale building model subject to several near-field earthquakes.